Seipin governs phosphatidic acid homeostasis at the inner nuclear membrane - Anete Romanauska; Edvinas Stankunas; Maya Schuldiner; Alwin Köhler (Nature Communications)
Abstract The nuclear envelope is a specialized subdomain of the endoplasmic reticulum and comprises the inner and outer nuclear membranes. Despite the crucial role of the inner nuclear membrane in genome regulation, its lipid metabolism remains poorly understood. Phosphatidic acid (PA) is essential for membrane growth as well as lipid storage. Using a genome-wide lipid biosensor screen in S. cerevisiae, we identify regulators of inner nuclear membrane PA homeostasis, including yeast Seipin, a known mediator of nuclear lipid droplet biogenesis. Here, we show that Seipin preserves nuclear envelope integrity by preventing its deformation and ectopic membrane formation. Mutations of specific regions of Seipin, some linked to human lipodystrophy, disrupt PA distribution at the inner nuclear membrane and nuclear lipid droplet formation. Investigating the Seipin co-factor Ldb16 reveals that a triacylglycerol binding site is crucial for lipid droplet formation, whereas PA regulation can be functionally separated. Our study highlights the potential of lipid biosensor screens for examining inner nuclear membrane lipid metabolism.